OPTIMALISASI PENGAWASAN INSPEKTORAT DAERAH DALAM PELAKSANAAN ANGGARAN DI MASA PANDEMIK COVID-19 DI SULAWESI TENGGARA - La Ode Ampera; Eka Suaib; Jamal Jamal (Universitas Halu Oleo, 2021)
This study aims to find out the form of optimizing the supervision of the Southeast Sulawesi regional inspectorate on budget implementation during the Covid-19 pandemic and to find out the results of the Southeast Sulawesi Regional Inspectorate's supervision of budget implementation during the Covid-19 pandemic. The method used in this study used a qualitative descriptive method. The results of this study indicate that the optimization of the supervision of the Southeast Sulawesi Province Inspectorate on the implementation of the use of the Covid-19 budget, shows that the Inspectorate's supervision on the management of the Covid-19 budget is going quite well. This can be seen from the development of the results of the supervision carried out during the evaluation period until the follow-up, there was an increase in findings from 3 recommendations to 10 administrative compliances. The results of the Supervision of Refocussing and Reallocating the Regional Budget to the Southeast Sulawesi Provincial Government showed that at the evaluation stage carried out by the Inspectorate, there were still many administrative and material negligence carried out by the Southeast Sulawesi government. The results of the Supervision of the Implementation and Designation of Handling in the Health Sector, Social Sector, and the Handling Economic Impact Sector from the Aspects of Timeliness, Quantity, and Quality, still found negligence in the implementation, this resulted in several recommendations that needed to be followed up immediately.AbstrakPenelitian ini bertujuan untuk mengetahui bentuk optimalisasi pengawasan inspektorat daerah Sulawesi Tenggara terhadap pelaksanaan anggaran dimasa Pendemik Covid-19 dan untuk mengetahui hasil pengawasan Inspektorat Daerah Sulawesi Tenggara terhadap pelaksanaan anggaran dimasa Pendemik Covid -19. Metode yang digunakan dalam penelitian ini menggunakan metode deskriptif kualitatif. Hasil penelitian ini menunjukan bahwa Optimalisasi pengawasan Inpektorat Provinsi Sulawesi Tenggara terhadap pelaksanaan penggunaan anggaran Covid-19, menunjukan bahwa pengawasan Inspektorat pada pengelolaan anggaran Covid-19 berjalan cukup baik. Hal ini, terlihatan dari pengembangan hasil pengawasan yang dilakukan pada masa evaluasi sampai pada tindak lanjut terjadi penambahan temuan dari 3 rekemndasi menjadi 10 kelalayan admnistrasi. Hasil Pengawasan Refocussing dan Realokasi APBD pada Pemerintah Provinsi Sultra menunjukan bahwa pada tahapan evaluasi yang dilakukan Inspektorat masih banyak menemukan kelalaian secara administrasi dan materil yang dilakukan oleh pemerintah Sulawesi Tenggara. Hasil Pengawasan terhadap Pelaksanaan dan Peruntukan Penanganan Bidang Kesehatan, Bidang Sosial, dan Bidang Penanganan Dampak Ekonomi dari Aspek Ketepatan Waktu, Jumlah, dan Kualitas, masih ditemukan kelalaian dalam pelaksanaannya hal ini mengakibatkan beberapa rekomendasi yang perlu segera ditindak lanjuti.